2021
DOI: 10.3390/jmmp5040102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sheets’ Thickness and Rivet Geometry on Mechanical Properties of Orbital Riveted Aluminium Joints: Experimental and Numerical Analysis

Abstract: Orbital riveting is an innovative joining technology used in various industrial fields. Despite its diffusion in recent years, it has not been accompanied by an equivalent interest from the scientific community, which has neglected the aspects of process optimization and joint performance. In this experimental/numerical study, six different configurations of orbital riveted joints were realised and tested to determine the effects of sheet thickness and rivet geometry on the mechanical properties of the joints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Another study by Di Bella et al [22] investigated the effects of some geometrical aspects such as sheet thickness and rivet diameter on aluminum joints produced by the orbital forming technique. The main results demonstrated that the symmetry in the joint geometry, by reducing bending phenomena, leads to unbuttoning during tensile tests.…”
mentioning
confidence: 99%
“…Another study by Di Bella et al [22] investigated the effects of some geometrical aspects such as sheet thickness and rivet diameter on aluminum joints produced by the orbital forming technique. The main results demonstrated that the symmetry in the joint geometry, by reducing bending phenomena, leads to unbuttoning during tensile tests.…”
mentioning
confidence: 99%